Angiotensin-converting enzyme 2: from a vasoactive peptide to the gatekeeper of a global pandemic. Issue 2 (31st March 2021) - Perico, Luca; Benigni, Ariela; Remuzzi, Giuseppe
Abstract : Purpose of review: We provide a comprehensive overview of angiotensin-converting enzyme 2 (ACE2) as a possible candidate for pharmacological approaches to halt inflammatory processes in different pathogenic conditions. Recent findings: ACE2 has quickly gained prominence in basic research as it has been identified as the main entry receptor for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). This novel pathogen causes Coronavirus Disease 2019 (COVID-19), a pathogenic condition that reached pandemic proportion and is associated with unprecedented morbidity and mortality. Summary: The renin–angiotensin system is a complex, coordinated hormonal cascade that plays a pivotal role in controlling individual cell behaviour and multiple organ functions. ACE2 acts as an endogenous counter-regulator to the pro-inflammatory and pro-fibrotic pathways triggered by ACE through the conversion of Ang II into the vasodilatory peptide Ang 1–7. We discuss the structure, function and expression of ACE2 in different tissues. We also briefly describe the role of ACE2 as a pivotal driver across a wide spectrum of pathogenic conditions, such as cardiac and renal diseases. Furthermore, we provide the most recent data concerning the possible role of ACE2 in mediating SARS-CoV-2 infection and dictating COVID-19 severity.